2020
DOI: 10.1097/jcma.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to health care services in migrants and potential strategies to improve accessibility: A qualitative analysis

Abstract: Background: While migrants in Taiwan are entitled to universal health care, barriers to health care services exist. We aimed to explore challenges encountered by migrants when accessing health care services and potential strategies to overcome these barriers. Methods: Invitations to participate in the study were sent to all hospitals, 12 migrant organizations, one language school, and one language service company in Taiwan, and convenience sampling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Davies, Basten and Frattini ( 2009 ), and Makandwa ( 2014 ) also reported that language is frequently cited as a major obstacle to the use of healthcare services, as there are no interpreters at the healthcare facilities. Kuan, Chen and Lee ( 2020 ) state that the influx of migrants who cannot communicate in English increases the demand for professional interpreters in healthcare facilities. It was also found in a study conducted by Amukugo, Nangombe and Karera ( 2020 ) from Namibia that the language barrier is complex in the healthcare process, more especially among healthcare providers who cannot communicate in the English language (Saburi 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Davies, Basten and Frattini ( 2009 ), and Makandwa ( 2014 ) also reported that language is frequently cited as a major obstacle to the use of healthcare services, as there are no interpreters at the healthcare facilities. Kuan, Chen and Lee ( 2020 ) state that the influx of migrants who cannot communicate in English increases the demand for professional interpreters in healthcare facilities. It was also found in a study conducted by Amukugo, Nangombe and Karera ( 2020 ) from Namibia that the language barrier is complex in the healthcare process, more especially among healthcare providers who cannot communicate in the English language (Saburi 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is the risk of unconscious bias acting as a barrier to equity of access through the offer, or lack of to RGCS. Whilst no access to technology barriers were reported, several HCPs raised concerns about potential consequences due to language barriers for couples from culturally and linguistically diverse backgrounds being able to access online material without HCP assistance [ 29 ]. The availability of online translation services may help overcome these concerns [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Although entitled to universal healthcare in Taiwan, migrant workers still experienced health disparities due to linguistic and financial barriers. 23 , 24 In respond to the pandemic, the Taiwanese government took a top-down approach to communicating with the public by putting out leaflets in different languages with information about COVID-19. Even with the government implementing intensive monitoring and prevention policies, the strategies were not immediately focused on migrant workers, 25 and the multilingual content was criticized for its symbolic multilingualism.…”
Section: Introductionmentioning
confidence: 99%